Systematic Suicide Audit: An Enhanced Method to Assess System Gaps and Mobilize Leaders for Prevention. Issue 2 (April 2021) - Fortin, Gabrielle; Ligier, Fabienne; Van Haaster, Ian; Doyon, Claude; Daneau, Diane; Lesage, Alain
Abstract : Background and Objectives: In Quebec, Canada, several independent processes are in place to investigate cases of death by suicide. An enhanced multidisciplinary audit process was developed to analyze these cases more thoroughly, with the aim of generating recommendations for suicide prevention. A study was undertaken to evaluate the feasibility and implementability of this process. Methods: The life trajectories of 14 people who died by suicide in Montreal, Canada, in 2016 were reconstructed on the basis of information retrieved by interviewing bereaved relatives and examining coroner investigation files and other records. A multidisciplinary panel that included a representative of families bereaved by suicide then reviewed case summaries to determine unmet needs and service gaps at 3 levels: individual intervention, regional programs, and the provincial health and social services system. Results: The feasibility of the audit process was demonstrated in the context of a public health care system. Thirty-one distinct recommendations were made variably across 13 of the 14 cases reviewed, whereas none had originally been made by the coroner. The recommendations that recurred most often were (1) improve training for professionals and educate the general public regarding depression and substance-related disorders; (2) deploy mobile crisis intervention teams from emergency departments; and (3) provide access to a family physician to all, especially men. Conclusion: Although the audit produced novel recommendations and is implementable, there was resistance from physicians and their hospital mortality review committee against this multidisciplinary audit involving families. These concerns could be alleviated by having the process endorsed by provincial authorities.